Promoting Green Finance through Multilateral Development Banks – The Experience of Romania - CLAUDIA GABRIELA BAICU; IULIA MONICA OEHLER-ŞINCAI (Global Economic Observer)
Achieving the ambitious climate goals established on the international agenda for boosting sustainable development involves significant financial resources. Therefore, the funds allocated by the financial system for green investments should increase globally. Against this backdrop our paper investigates the role of multilateral development banks in promoting green finance, with focus on Romania. The research results underline their engagement to combat climate change and to support sustainable development. The European Investment Bank, The European Bank for Reconstruction and Development and the International Finance Corporation have major contributions in financing green projects in Romania in areas such as energy efficiency, green building, clean transportation, sustainable agriculture. To this end they established some partnerships with Romanian financial institutions, granted financing facilities, invested in the green bonds issued by local banks, provided technical assistance. However, our main finding shows that green finance in Romania is still limited, requiring increased commitments in this area, including from multilateral development banks.